COMPARISON OF THE RESULTS OF CALCULATION OF THE STEEL SLUGS HEATING IN FURNACE WITH PACING BACKSTONE WITH THE EXPERIMENTAL DATA - V. I. Timoshpolskij; M. L. German; P. S. Grinchuk; S. M. Kabishov; S. V. Korneev (Литьë и металлургия)
The comparison of the results of the temperature regimes of the heating furnace with pacing backstone with experimental data, received in terms of operating production at working of furnace with varied capacity is carried out.